2015
DOI: 10.1016/j.virol.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of non-reciprocal heterologous immunity between unrelated viruses

Abstract: Heterologous immunity refers to the phenomenon whereby a history of an immune response against one pathogen can provide a level of immunity to a second unrelated pathogen. Previous investigations have shown that heterologous immunity is not necessarily reciprocal, such as in the case of vaccinia virus (VACV). Replication of VACV is reduced in mice immune to a variety of pathogens, while VACV fails to induce immunity to several of the same pathogens, including lymphocytic choriomeningitis virus (LCMV). Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 42 publications
0
19
0
1
Order By: Relevance
“…Such a situation of preexisting partial immunity to a pathogen can also occur in a primary infection when a pathogen happens to share an epitope with a previously encountered unrelated pathogen—a phenomenon known as heterologous immunity (Welsh et al., 2010, Che et al., 2015). Though highly relevant for understanding immunity in humans, interferences between past and present infections (or vaccinations) are rarely investigated under well-defined conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Such a situation of preexisting partial immunity to a pathogen can also occur in a primary infection when a pathogen happens to share an epitope with a previously encountered unrelated pathogen—a phenomenon known as heterologous immunity (Welsh et al., 2010, Che et al., 2015). Though highly relevant for understanding immunity in humans, interferences between past and present infections (or vaccinations) are rarely investigated under well-defined conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies on heterologous immunity have shown that when T cell crossreactivity between two pathogens occurs, it may depend on the order of the infection sequence and that it does not necessarily occur in all individuals, due to the private specificity of their TCR repertoires (22,23,64). This was dramatically illustrated in this study where the cross-reactivity was detected only in the MCMVϩLCMV sequence (not LCMVϩMCMV), and when it did occur, it was observed approximately in only one of every five MCMV-immune mice.…”
Section: Discussionmentioning
confidence: 99%
“…with 5 ϫ 10 5 PFU of MCMV or given salivary gland homogenate from naive mice as controls. Memory CD8 T cells specific for GP [33][34][35][36][37][38][39][40][41] , NP 396 -404 , and GP 118 -125 , (a to d) and memory CD4 T cells specific for GP [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] from the spleen (e) were examined at weeks 6, 12, 23, and 48 post-MCMV infection by ICS (n ϭ 5). The complete experiment was done once, but a similar observation was made in a separate experiment in cells harvested at weeks 9 and 24 post-MCMV inoculation.…”
mentioning
confidence: 99%
“…Of note, HI may alter the immunodominance, induce changes in polarisation or result in loss of speci c T m cells [28]. In addition, heterologous immune responses are not necessarily reciprocal [40].…”
Section: Heterologous Immunitymentioning
confidence: 99%